Pemberdayaan Kader dalam Aplikasi, Sosialisasi DDTK (Deteksi Dini Tumbuh Kembang) dan Anticipatory Guidance di Kecamatan Wonodadi - Erni Setiyorini; Yeni Kartika Sari (STIKes Patria Husada Blitar, 2015)
In Indonesia, the number of infants reach 10% of the population, in which the prevalence of development disorder 12,8%–16% and we need to screening development of children. The mortality of childrens high due to accident, poisoning and trauma recorded 7,3% and one of top five lead child deaths in 1992. Based on interviews with some kader posyandu, we know that the kader had never received training related to early detection growth and development and anticipatory guidance in children. The purpose of this science and technology activity for society was to empower kader in the application, the socialization of children’s early detection growing and development Method for this activity was to team up with 2 partners i.e. Midwife of Kebonagung Village with number of kader of 25 people and the midwife of Wonodadi village with number of cadres of as many as 30 people. The method of this activity was to provide a pre test training before, children’s early detection growth and development with method of lecture, discussion, simulation and applications of valuation DDTK in kindergarten, mentoring and evaluation of training activities and the activities of the posyandu. The results of the evaluation of the training process showed improved knowledge on average level of good on both of kader and partner, most cadres is skilled, whereas the evaluation of the activities of mentoring at posyandu activities, most of posyandu already documenting the measurement of height, weight, nutritional status, while for childrens’s early detection growing and development with developmental screening assessment card but not complete. In order for the assessment, documentation, socialization of childrens’s early detection growing and development activities and anticipatory guidance fluently, then the expected partner, the Councilor and head of the Clinic Wonodadi made a commitment in the monitoring activities.